Big data analytics for sustainable computing - Haldorai, Anandakumar, 1983-, editor 631908; Ramu, Arulmurugan, 1985-, editor 631909 (Hershey, PA : Engineering Science Reference, an imprint of IGI Global, 2020)
"This book addresses significant computing and related system development issues in the emerging sustainable application domains".